Kinetic Investigations of Boronized Cold Work Tool Steels - Topuz, Polat; Yilmaz, Eren; Gundogdu, Emine (CARL HANSER VERLAG, 2014)
In this study, kinetic examinations on boronized X45NiCrMo4 (DIN 1.2767) and 90MnCrV8 (DIN 1.2842) steel samples are described. Samples were boronized in indirect heated fluidized bed furnace at 1123 K, 1223 K, and 1323 K for 1 h, 2 h, and 4 h. Morphologically and typically examinations of borides formed on the surface of the steel samples were studied by optical microscope, scanning electron microscope (SEM), and X-ray diffraction (XRD). Boride layer thickness formed on the steel X45NiCrMo4 ranges from 45 mu m to 382 mu m and for the material 90MnCrV8 ranges from 33 mu m to 471 mu m. The hardness of the boride layer formed on the steel X45NiCrMo4 varied between 1713 HV0.1 and 2111 HV0.1 and for the steel 90MnCrV8 between 1716 HV0.1 and 2761 HV0.1. Layer growth kinetics were analyzed by measuring the extent of penetration of FeB and Fe2B sublayers as a function of boronizing time and temperature. The kinetics of the reaction has been determined with K = K-o exp (-Ct/RT) equation. Activation energy (G) of the bonded steel X45NiCrMo4 was determined as 156 kJ/mol and that of the steel 90MnCrV8 was determined as 179 kJ/mol.
Keywords: Materials Science